Prioritizing High-Risk Practices and Exploring New Emerging Ones Associated With Hepatitis C Virus Infection in Egypt. - Ammal Metwally; Amira Mohsen; Rehan Saleh; Walaa Foaud; Nihad Ibrahim; Thanaa Rabaah; Manal El-Sayed (Tehran University of Medical Sciences, 2014)
The aim of this study was to identify and prioritize the risky behaviors and explore the newly emerging pi related to Egyptian habits that may lead to HCV transmission.From January 2011 until January 2012, a case control study matched on socio demographic factors was conducted comparing 540 hepatitis C patients and their contacts who were HCV serologically negative (102 subjects). They were randomly selected from six governorates representing Upper Egypt, Lower Egypt, Middle and Canal regions. The questionnaire covered demographic data, risk exposures, behaviors, and practices for HCV infection. Focus group discussions were done with groups of professionals in Hepatology to discuss the observed emerging risk practices in Egypt.In univariate analysis, invasive medical procedures, wound stitches, illiteracy and marriage were significantly associated with HCV infection. Among women, delivery at home by traditional birth attendant was associated with 3 times (OR=2.91, CI=1.23-6.98) and 4 times (OR=3.94, CI=1.44-11.35) increase in HCV risk than delivery at hospital and by doctors respectively. Among males, shaving at barbershops was associated with 2 fold increase in the risk of infection (OR=2.6, CI=1.44-4.89). Newly observed emerging risk practices were: sharing scarves' pins by veiled women in same houses, sharing loofah for personal cleaning and sharing toothpaste among family members.Increasing risk of HCV infection in Egypt reinforces the need for strict implementation of effective HCV prevention programs according to the prevailing risk behaviours.